Econometric Forecasting models for Air Freight in Indonesia (And How Will It be Affected by COVID-19?) - Viktor Suryan; Anggi Nidya Sari; Direstu Amalia; M. Fathar Habillah (Journal of Airport Engineering Technology (JAET), 2020)
Forecasting using the economic factor as indicators seems significant related. The experts also suggest predict the number of traffic in transport by approaching the econometric models. This paper predicting the upcoming number of air freight until 2030. The result shows GDP is significant related to number of air freight. However, the economic crisis also contributes to decreasing the value. Also, the Covid-19 impact the economic in the country. Predicting the number of air freight in 2020 is going down. The number seems gradually grow after two years and assume the pandemic is over soon